2018
DOI: 10.1038/s41417-018-0035-0
|View full text |Cite
|
Sign up to set email alerts
|

miR-140-5p inhibits the proliferation and enhances the efficacy of doxorubicin to breast cancer stem cells by targeting Wnt1

Abstract: MicroRNAs (miRNAs) are a group of small non-coding single-stranded RNAs molecules, the dysregulation of which plays a critical role in the initiation and biological progression of malignancies. The current study demonstrated that miR-140-5p was frequently downregulated in breast cancer stem cells (BCSCs), and miR-140-5p mimics could inhibit the proliferation of BCSCs. Moreover, Wnt1 was a direct target of miR-140-5p, as was proved by luciferase reporter assays. miR-140-5p mimics could downregulate the wnt1 mRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 31 publications
2
32
0
Order By: Relevance
“…The expression of miR-93 was upregulated, and cell proliferation was promoted in the insulin-stimulated KGN granulosa cells [10]. In recent years, miR-140 has been reported to exhibit significant regulatory effects with respect to cell proliferation, differentiation, migration, and invasion [11][12][13]. Scalici et al showed that the expression of miR-140 in the follicular fluid was different between PCOS and normal ovarian reserves, with a specificity of 83.8% and a sensitivity of 70% [14].…”
Section: Introductionmentioning
confidence: 99%
“…The expression of miR-93 was upregulated, and cell proliferation was promoted in the insulin-stimulated KGN granulosa cells [10]. In recent years, miR-140 has been reported to exhibit significant regulatory effects with respect to cell proliferation, differentiation, migration, and invasion [11][12][13]. Scalici et al showed that the expression of miR-140 in the follicular fluid was different between PCOS and normal ovarian reserves, with a specificity of 83.8% and a sensitivity of 70% [14].…”
Section: Introductionmentioning
confidence: 99%
“…25,26 The expression of miR-140 is decreased in breast cancer stem cells (BCSCs), and miR-140 acts as a tumour suppressor gene to inhibit tumour proliferation by regulating Wnt1. 27 It has been reported that miR-185 expression is downregulated in some tumours and that upregulation of miR-185 expression significantly inhibits the growth, migration, and invasion of Ewing's sarcoma cells. Inconsistent with miRNA microarray results, the expression levels of miR-4505 and miR-4741 were higher in myeloma exosomes than HCs.…”
Section: Discussionmentioning
confidence: 99%
“…Mimics of miRNA-140-5p enhanced sensitivity of doxorubicin treatment via the Wnt1/ABCB1 pathway both in vitro and in vivo. Therefore, these findings would suggest increased miRNA-140-5p expression levels may benefit patient response to doxorubicin treatment and reduce chemoresistance [150].…”
Section: Induced Mirna-140-5p Levels In Breast Cancer May Enhance Outmentioning
confidence: 95%
“…Expression of miRNA-140-5p is frequently down regulated in breast cancer stem cells and its inhibitory effects on proliferation have been linked to Wnt1 [150]. Mimics of miRNA-140-5p enhanced sensitivity of doxorubicin treatment via the Wnt1/ABCB1 pathway both in vitro and in vivo.…”
Section: Induced Mirna-140-5p Levels In Breast Cancer May Enhance Outmentioning
confidence: 99%